Russia and the western far right : tango noir - Šechovcov, Anton 1978- (Routledge studies in fascism and the far right, 2018)
Soviet Russia in the western far right perspective : ideology, collaboration, active measures -- Russia's opening to the western far right -- Putin's Russia, an authoritarian kleptocracy with a twist -- Far right election observers in the service of the Kremlin's domestic and foreign policies -- Undermining the West through mass media -- Far right structures in Europe as pro-Moscow front organisations -- The Moscow-Strasbourg-Brussels axis